2001
DOI: 10.1017/s002211200000313x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a drag reduction on a circular cylinder in rotary oscillation

Abstract: Drag reduction in two-dimensional flow over a circular cylinder, achieved using rotary oscillation, was investigated with computational simulations. In the experiments of Tokumaru & Dimotakis (1991), this mechanism was observed to yield up to 80% drag reduction at Re = 15 000 for certain ranges of frequency and amplitude of sinusoidal rotary oscillation. Simulations with a high-resolution viscous vortex method were carried out over a range of Reynolds numbers (150-15 000) to explore the effects of oscillatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 23 publications
5
41
0
Order By: Relevance
“…The vortex shedding just behind the cylinder seems to be mainly attributed to increased vorticity in the shear layer due to the rotational oscillation of the cylinder. As mentioned by Shiels and Leonard (2001), the drag reduction effect seems to be due to separation delay resulting from a multipole vorticity structure. Their results match well with the drag reductions observed here for F R o1.0 and the strong influence of vortex shedding, as shown in Figs.…”
Section: Article In Pressmentioning
confidence: 78%
See 1 more Smart Citation
“…The vortex shedding just behind the cylinder seems to be mainly attributed to increased vorticity in the shear layer due to the rotational oscillation of the cylinder. As mentioned by Shiels and Leonard (2001), the drag reduction effect seems to be due to separation delay resulting from a multipole vorticity structure. Their results match well with the drag reductions observed here for F R o1.0 and the strong influence of vortex shedding, as shown in Figs.…”
Section: Article In Pressmentioning
confidence: 78%
“…Moreover, they observed a phase change of approximately 1801 between the cylinder motion and the vortex shedding when the forcing frequency crossed the natural Karman frequency. In a study of the drag reduction mechanism and its effects, Shiels and Leonard (2001) showed that the reduction in drag was a result of separation delay due to the presence of a multipole vorticity structure in the boundary layer above the oscillating cylinder. They also found that the rotational oscillation technique is effective only at high Reynolds number (ReX3000).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental work of Tokumaru and Dimotakis 7 demonstrated the potential for this control method to affect the flow-field and reduce the drag of a cylinder by up to roughly 80% at Re = 1.5 × 10 4 and has prompted many other authors to investigate the effect of oscillatory cylinder rotation on the development of the vortex street at different Reynolds numbers, e.g., Refs. [16][17][18][19][20]. In these studies, the cylinder's sinusoidal rotation needs to be vigorous for the control to successfully reduce drag: typically, the amplitude of the tangential velocity on the cylinder surface is several times larger than the inflow velocity, and the Strouhal number associated with the cylinder rotation is of the order of St = f D/U ∞ = 1, where f is the dimensional frequency.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Fig. 6(c) shows numerous small-scale vortices distributed along the shear layers, which resemble the topological vorticity pattern for which Shiels and Leonard (2001) observed the maximum drag reduction effect in the rotationally oscillating circular cylinder. This kind of near-wake flow pattern is occasionally observed in flows in which the vortex shedding mode changes intermittently.…”
Section: Article In Pressmentioning
confidence: 62%
“…Mahfouz and Badr (2000) found that the lock-on phenomenon occurred when the forcing frequency was close to the natural shedding frequency, and that the lock-on frequency range widened as the oscillation amplitude was increased. Shiels and Leonard (2001) observed that the drag was reduced as a result of separation delay due to the presence of multipole vorticity structures in the boundary layer around an oscillating cylinder, and that the rotational oscillation method for drag reduction was effective only at high Reynolds numbers (ReX3000). Dennis et al (2000) and Poncet (2004) investigated the temporal variation of the large-scale vortex structure behind a rotationally oscillating cylinder at moderate Reynolds numbers with varying forcing conditions.…”
Section: Introductionmentioning
confidence: 99%